2017
DOI: 10.1007/s11356-017-9588-y
|View full text |Cite
|
Sign up to set email alerts
|

Interrelationship between silicon, aluminum, and elements associated with tissue metabolism and degenerative processes in degenerated human intervertebral disc tissue

Abstract: There is a growing body of evidence concerning the significant role of silicon in development and composition of both connective and bone tissue. Bio-essential silicon shows strong chemical and biological affinity to aluminum, which is toxic and biologically inessential element. The presence of silicon was confirmed in a variety of tissues; however, it has never been examined in intervertebral disc tissue, neither in healthy nor in degenerated one. In this paper, for the first time in the literature, we presen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…Cuproptosis is a copper-triggered manner of mitochondrial cell death [ 38 ]. Mounting evidence has revealed that copper metabolism plays an important role in multiple biological processes of IDD [ 14 , 39 ]. It has been verified that copper complexes exert a toxic and immunogenic effect on intervertebral discs [ 15 ], suggesting that cuproptosis may exist in the pathological process of IDD.…”
Section: Discussionmentioning
confidence: 99%
“…Cuproptosis is a copper-triggered manner of mitochondrial cell death [ 38 ]. Mounting evidence has revealed that copper metabolism plays an important role in multiple biological processes of IDD [ 14 , 39 ]. It has been verified that copper complexes exert a toxic and immunogenic effect on intervertebral discs [ 15 ], suggesting that cuproptosis may exist in the pathological process of IDD.…”
Section: Discussionmentioning
confidence: 99%
“…The quantitative analysis of the content of trace elements in the human intervertebral discs affected by the degenerative process is of significant importance [ 16 ]. It should be remembered that some of the elements, such as copper, zinc, and magnesium, participate in the metabolic processes, while others, such as lead and cadmium, provide information about exposure to environmental pollutants and have accumulative properties in the examined tissue.…”
Section: Discussionmentioning
confidence: 99%
“…One of the most important causes of changes in the internal environment leading to IVDD can be changes in the concentration of individual metal elements. Performing a quantitative analysis of the elements present in the intervertebral disc, in which degeneration occurs, enables the identification of the metals that may significantly affect the progression of degenerative changes, or the regeneration of the damaged intervertebral disc [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…The mechanism by which these cement extracts affect collagen type I synthesis is likely associated with silicon regulation of prolyl-hydroxylase activity, an enzyme required for collagen cross-linking [39]. Silicon is a ubiquitous environmental element that binds to glycosaminoglycans, playing a role in cross-linking of this molecule with collagen and preventing enzymatic degradation, and promoting collagen stabilisation [40]. However, further studies are required to explore the exact mechanism.…”
Section: Discussionmentioning
confidence: 99%